Deep Sequencing for Evaluation of Genetic Stability of Influenza A/California/07/2009 (H1N1) Vaccine Viruses. - Majid Laassri; Tatiana Zagorodnyaya; Ewan P Plant; Svetlana Petrovskaya; Bella Bidzhieva; Zhiping Ye; Vahan Simonyan; Konstantin Chumakov (PLoS ONE, 2015)
Virus growth during influenza vaccine manufacture can lead to mutations that alter antigenic properties of the virus, and thus may affect protective potency of the vaccine. Different reassortants of pandemic "swine" H1N1 influenza A vaccine (121XP, X-179A and X-181) viruses as well as wild type A/California/07/2009(H1N1) and A/PR/8/34 strains were propagated in embryonated eggs and used for DNA/RNA Illumina HiSeq and MiSeq sequencing. The RNA sequences of these viruses published in NCBI were used as references for alignment of the sequencing reads generated in this study. Consensus sequences of these viruses differed from the NCBI-deposited sequences at several nucleotides. 121XP stock derived by reverse genetics was more heterogeneous than X-179A and X-181 stocks prepared by conventional reassortant technology. Passaged 121XP virus contained four non-synonymous mutations in the HA gene. One of these mutations (Lys226Glu) was located in the Ca antigenic site of HA (present in 18% of the population). Two non-synonymous mutations were present in HA of viruses derived from X-179A: Pro314Gln (18%) and Asn146Asp (78%). The latter mutation located in the Sa antigenic site was also detected at a low level (11%) in the wild-type A/California/07/2009(H1N1) virus, and was present as a complete substitution in X-181 viruses derived from X-179A virus. In the passaged X-181 viruses, two mutations emerged in HA: a silent mutation A1398G (31%) in one batch and G756T (Glu252Asp, 47%) in another batch. The latter mutation was located in the conservative region of the antigenic site Ca. The protocol for RNA sequencing was found to be robust, reproducible, and suitable for monitoring genetic consistency of influenza vaccine seed stocks.